The legal regulation of surrogate motherhood in Kazakhstan (International relations and international law Journal, 2018)
The article deals with actual problems of modern society, the achievement of medicine on the wayto become genetic parents as a surrogate motherhood. The author explores the definition and types ofsurrogate motherhood (partial and complete, traditional and non-traditional); what are the requirementsfor a surrogate mother? Whether surrogate motherhood is permitted in Kazakhstan and abroad; whatpeople can use the service of a surrogate mother (commercial or non-commercial basis).The author analyzed the provision of surrogate motherhood services in Kazakhstan and abroad andidentified the strengths and weaknesses side of the legislation. Gives a list of countries where auxiliaryreproductive technology is legally permitted and prohibited, shows the reasons for not providing thisservice. Much attention is given to the rights of a surrogate mother during the pregnancy and child. ComparingKazakhstan and international laws, the author has revealed ways of improving the legal regulationof surrogate motherhood.During the investigation, the following conclusions were made: who can be a surrogate mother, andwhat requirements does she have to meet? Citizens of the Republic of Kazakhstan and foreign citizenshave the right to use the service of a surrogate mother in the territory of Kazakhstan; the rules for concludinga surrogate mother contract.Key words: The Republic of Kazakhstan, the Surrogate Mother, Contract.